Take It from the Big Mouth : The Life of Martha Raye - Pitrone, Jean Maddern, 1920-2008 (Book collections on Project MUSE., 1999)
""She was one of the world's four best comediennes, "" said Milton Berle, ""but she lived a life of personal disaster."" Martha Raye sang, danced, and joked her way into the spotlight of the entertainment world with a career that spanned seven decades and encompassed everything from vaudeville to television commercials to entertaining U.S. troops. Take It from the Big Mouth, the first full-fledged biography of the multi-talented performer, explores Raye's life and career with candor and insight. Raye got her big break when she caught the attention of a film director as she kidded with audience.